Analysis of the status of social frailty in Chinese older adults with cardiovascular and cerebrovascular diseases: a national cross-sectional study - Qi, Xin; Jia, Na; Hu, Jiabin; Meng, Ling-bing; Zeng, Ping; Liu, Junmeng; Shi, Jing; Zeng, Xuezhai; Li, Hui; Zhang, Qiuxia; Li, Juan; Liu, Deping (Frontiers in Public Health, 2023)
Background: Social frailty is one type of frailty. Physical frailty with cardiovascular and cerebrovascular diseases (CCVD) have been studied a lot, but less research on social frailty. Objectives: To study the prevalence, related risk factors and regional differences of social frailty with CCVD in Chinese elderly. Methods: SSAPUR was a national cross-sectional survey. Participants aged 60 years or older were recruited in August 2015. Demographic data and information regarding family, health and medical conditions, living environment conditions, social participation, spiritual and cultural life, and health condition were obtained. Social frailty was assessed in five areas (HALFE Social Frailty Index) including inability to help others, limited social participation, loneliness, financial difficulty, and living alone. The prevalence of CCVD with social frailty, related risk factors and regional differences in CCVD with social frailty were studied. Results: A total of 222,179 participants were enrolled. 28.4% of them had CCVD history. The prevalence of social frailty in the CCVD group was 16.03%. In CCVD participants, compared with the group without social frailty, there were significant differences in gender, age, urban-rural distribution, ethnicity, marital status, and education levels in the social frailty group. Significant differences were also found in physical exercise participation, health status, cataract, hypertension, diabetes mellitus, hospitalization within one year, self-assessed health status, crutch or wheelchair usage, urinary and fecal incontinence, need for care from others, fall history, housing satisfaction, and self-assessed happiness in the social frailty group. Women with CCVD had a higher prevalence of social frailty than men. By age in CCVD with social frailty, the highest prevalence was found in participants 75-79 years old. The prevalence of CCVD was significant difference between social frailty in urban and rural group. The prevalence of social frailty with CCVD was significantly different in different regions. The highest prevalence was 20.4% in southwest area, and the lowest prevalence was 12.5% in northeast with area. Conclusions: The prevalence of social frailty among the CCVD elderly is high. Factors such as gender, age, region, urban-rural residence, and the state of the disease may be associated with social frailty. Keywords: Social frailty, Older adults，Cardiovascular and cerebrovascular diseases，Chinese